THE IMPLEMENTATION OF TEACHING ENGLISH VOCABULARY USING VISUAL AIDS TO THE SIXTH YEAR STUDENT OF SDN 5 PURWOSUMAN SRAGEN IN 2006 - SUTRISNO , AGUS (2007)
This research aims at describing the implementation of teaching English vocabulary using visual aids to the sixth year students of SDN 5 Purwosuman Sragen. The problem is how the teaching vocabulary using visual aids and the problem faced by the teacher. The writer uses descriptive qualitative as the type of the research. The data used in this research are derived from observation, interview, questionnaire, and translation. Based on the data analysis the outcomes are: Firstly, the implementation teaching English vocabulary using visual aids is divided into three main sections (1) The goal of learning. To get the goal of learning, the teacher using visual aids as teaching media for teaching English vocabulary. (2) The syllabus model. The syllabus in this research is thematic syllabus. (3) The procedure of teaching learning process. It’s divided into three main discussions; Classroom activity covers discussion on the teaching and learning process. Teacher’s role includes the function of the teacher when teacher does th e work as a teacher. Learner’s role describes the students responsibility as a learner.